Cause - consequence analysis of human-wildlife conflict in Wayanad district, Kerala - Ajaisanker K (Department of Forest Management and Utilization, 2017)
Human-wildlife conflicts is now a paradox for foresters and policy makers across the globe. In Kerala, interaction between humans and wildlife is affecting many lives and livelihoods. The damage caused by these interactions are drastic, it can vary from crop loss in a small area to human deaths. For the people living near the protected areas crop losses and livestock losses due to raiding by wildlife are a serious social and ecological concern as this can create an anti-wildlife lobby in the long run. So, understanding the social dimensions of such conflicts is also important to frame effective mitigation strategies. The study titled “Cause-consequence analysis of human-wildlife conflict in Wayanad district, Kerala” conducted during 2015-2017 tried to discern the nature, frequency, distribution and intensity of human-wildlife conflicts in Wayanad district and to understand the causative factors involved in the conflicts. The study was also intended to suggest suitable mitigatory measures to enhance human-wildlife coexistence in Wayanad district. A total of 120 households were interviewed from four locations in Wayanad namely Meppadi, Odapallam (SulthanBathery), Bhoothanam (Chedleth) and Thirunelli. Detailed interviews using pre-tested questionnaire was conducted and Participatory Rural Appraisal (PRA) tools like timeline, problem tree and vulnerability mapping was employed at each location for collecting additional information. Crop raiding was found to be the major type of conflict occurring in the district. Over the past years there occurred a shift in the farming practices with banana becoming a popular crop at the expense of the traditional crops. Most of the respondents lived in the close proximity and practiced agriculture and also occasionally integrated livestock in their farms. More palatable crops in the forest fringes along with domestic animals and plentiful water attracted the wildlife to the farmlands. Plantations of teak, eucalyptus etc, together with the invasive alien weed species has smothered the natural vegetation thereby reduced the natural food resources triggering animal migration. Reduced rainfall, droughts and forest fires that the district now increasingly experience has further reduced the availability of resources for the wildlife. These were found to be the major causes leading to conflicts. People were well aware of the forest laws and the attitude of the farmers to wildlife was positive. They believed in coexistence and conservation to be unavoidable for human existence. Enrichment of the habitat and fencing around the farmlands were favoured as the best mitigation measure. People did support the compensation schemes and insurances, provided they were adequate and immediate. The study outlines the possible role of various stakeholders such as farmers, Non- Governmental Organisations, Research institutions, Local self-governmental institutions and governments in improving the conflict mitigation process.